Manajemen Pembelajaran Kolaboratif Melalui Integrasi Teknologi dalam Implementasi Kurikulum Merdeka Sebagai Inovasi Pembelajaran di SMP N 2 Kota Bengkulu - Citra Dewi; Suwarni; Feby Elra Perdima; Juwita; Hendri Alamsyah; Dariusman; Hebrian Ananda (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2024)
Collaborative learning is learning that places students with diverse backgrounds and abilities working together in small groups to achieve common goals. There are several characteristics of collaborative learning, namely: (1) positive dependence, (2) interaction (face to face), (3) individual and group accountability, (4) development of interpersonal skills (5) formation of heterogeneous groups, (6) sharing knowledge between teachers and students, (7) sharing authority or roles between teachers and students, and (8) teachers as mediators. Collaborative learning is in accordance with the constructivism ideology. According to the constructivism ideology, knowledge cannot be transferred from teacher to student, but must be actively constructed by students themselves. In this community service, the Dehasen Bengkulu University Lecturer Team provided assistance/socialization related to Collaborative Learning Management through technology integration in the implementation of the independent curriculum as a form of learning innovation at SMPN 2 Bengkulu City. This activity aims to increase knowledge for teachers at SMPN 2 Bengkulu City to be able to further develop varied and student-centered learning. Through collaborative learning, students can provide each other with intellectual guidance that allows them to work on more complex tasks. This would be difficult to achieve if students did it individually.